(untitled) - Burd, Barry (New Jersey, 2005)
Covering everything from basic Java development concepts to the latest tools and techniques used in Java, this book will put would-be programmers on their way to Java mastery. Explores what goes into creating a program, how to put the pieces together, dealing with standard programming challenges, debugging, and making it work and Updated for the release of the Java SDK 2.0, with all examples revised to reflect the changes in the technology.
Keywords: Java (computer program language)